Prevalence and causes of blindness in patients coming to a tertiary eye care centre in western Uttar Pradesh - Priya, Manu; Mehrotra, Neelima; Tripathi, Shipra; Singh, Kunwar G.; Mishra, Ram M.; Agarwal, Aastha (International Journal of Research in Medical Sciences, 2023)
Background: Objective of the research was to study the prevalence of blindness in adult patients coming to a tertiary eye care centre in Western Uttar Pradesh and assess their causes. Methods: A cross-sectional study was conducted on adult patients coming to the outpatient department of a tertiary eye care centre over a period of 3 months and 375 patients were identified as having blindness. Complete ophthalmological examination was conducted to find out the cause for the same. Results: The prevalence of blindness was found out to be 4.096%. The major causes for blindness in adults were identified as cataract (33.06%), glaucoma (13.6%), ARMD (5.6%), diabetic retinopathy (5.06%), corneal scar/opacity/dystrophy (26.93%), amblyopia (3.2%) and trauma (2.13%). Conclusions: Knowledge of prevalence of blindness in a region is important in developing and implementing eye care services. Avoidable blindness needs to be identified and treated as soon as possible.